New paradigms in library management and knowledge generation - Lozano, Roser (Anuario ThinkEPI, 2012)
The main issues covered at the seminar "New paradigms in the management of public libraries: library and social development", held at the Cultural Office of the Spanish Embassy in Caracas (Venezuela) are discussed, highlighting two key issues: the contrast between American and European models of library systems, and the growing importance of the "multiauthority" concept.